2007
DOI: 10.1038/ni1457
|View full text |Cite|
|
Sign up to set email alerts
|

Toll-like receptor 9–dependent activation by DNA-containing immune complexes is mediated by HMGB1 and RAGE

Abstract: Increased concentrations of DNA-containing immune complexes in the serum are associated with systemic autoimmune diseases such as lupus. Stimulation of Toll-like receptor 9 (TLR9) by DNA is important in the activation of plasmacytoid dendritic cells and B cells. Here we show that HMGB1, a nuclear DNA-binding protein released from necrotic cells, was an essential component of DNA-containing immune complexes that stimulated cytokine production through a TLR9-MyD88 pathway involving the multivalent receptor RAGE.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
1,070
5
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,232 publications
(1,132 citation statements)
references
References 63 publications
27
1,070
5
12
Order By: Relevance
“…RAGE in adaptive immune responses HMGB1 interaction with RAGE activates plasmacytoid dendritic cells and B cells in response to DNA-containing immune complexes and thus contributes to autoimmune pathogenesis [74]. Activation of innate immune responses may alter the way in which antigens are presented to T and other cells of the adaptive immune response.…”
Section: The Role Of Rage In Various Pathological Settingsmentioning
confidence: 99%
“…RAGE in adaptive immune responses HMGB1 interaction with RAGE activates plasmacytoid dendritic cells and B cells in response to DNA-containing immune complexes and thus contributes to autoimmune pathogenesis [74]. Activation of innate immune responses may alter the way in which antigens are presented to T and other cells of the adaptive immune response.…”
Section: The Role Of Rage In Various Pathological Settingsmentioning
confidence: 99%
“…Necrotic cells, especially those derived from cancer tissues, release passivelly HMGB1 protein, which mediates regional inflammation and the development of cancer (Scaffidi et al, 2002;Luo et al, 2012). Extracellular HMGB1 protein interacts with several receptors including the receptors for advanced glycation end products (RAGE), Toll-like receptors (TLR) and CD24 (Tian et al, 2007). It has been reported that HMGB1 and RAGE were overexpressed in ccRCC.…”
Section: Introductionmentioning
confidence: 99%
“…The change of autoantibody and pro-inflammation cytokine levels in serum and urine, the monocyte chemotactic protein-1 (MCP-1) expression in kidney and the B cell activating factor (BAFF) (11)(12)(13)(14)(15) expression in spleen, all of which may play a role in the development of lupus nephritis, was also determined to explore the mechanism of action of artesunate.…”
Section: Introductionmentioning
confidence: 99%